Spatial Interaction Based on Sub-District Development Index in Pandeglang Regency - Okta Wulandono; Ernan Rustiadi; Muhammad Ardiansyah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
Population movement is a form of spatial interaction between regions. This phenomenon arises asa logical consequence of the heterogeneity of regional development that occurs. PandeglangRegency as an underdeveloped area should not be left behind because of the many leaks of spatialinteractions that are more directed outside this district. Investigating the daily mobilization of thepopulation internally is important in determining which sub-districts play a role as a destination foreconomic activity. The basic data used include the survey origin destination of Banten Province in2019 and data on Potential Villages (Podes) 2019 in the Pandeglang Regency. The method used isthe Scalogram method to determine the Sub-District Development Index (SDI) and the gravitymethod to analyze spatial interactions. The Hierarchical classification was carried out on the SDIvariable, the number of daily movements (density), and the distance between districts. This is doneto see the intensity of the daily movement of the population according to density, distance, andSDI hierarchy class. The spatial interaction magnitude is estimated based on the populationestimation parameters and SDI through the natural logarithmic transformation (ln) of the gravitymethod formula. The results show that the highest average population movement occurs in thehigh-density hierarchy leading to the sub-districts of the SDI 1 hierarchy. The sub-districts ofCadasari, Munjul, Patia, Saketi, and Sukaresmi as sub-districts from which spatial interactionoriginate will produce positive intensity values when compared to other sub-districts. CadasariSub-District will provide a positive spatial interaction value when it becomes the goal of the dailymovement of the population.